Telaah Al-Qur'an terhadap Landasan dan Tujuan Pendidikan Islam - Ade Budi; Mulyanah Mulyanah (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2026)
The Qur'an serves as the primary source of guidance for Muslims, providing comprehensive principles that govern both individual and social life, including the foundations and objectives of education. Amid rapid social transformation, scientific advancement, and the growing complexity of contemporary educational challenges, reexamining the Qur'anic foundations of Islamic education has become increasingly important to ensure its continued relevance while preserving its normative values. This study aims to analyze the foundations and objectives of Islamic education from the perspective of the Qur'an and to examine their implications for contemporary Islamic educational practices. Employing a qualitative library research approach and content analysis of Qur'anic verses, classical and contemporary Qur'anic exegeses, and relevant scholarly literature, the study reveals that the Qur'an establishes divine revelation as the primary foundation of Islamic education, complemented by the Sunnah and ijtihad as dynamic sources for addressing evolving societal needs. Furthermore, the objectives of Islamic education encompass the development of individuals who possess faith, knowledge, and noble character, fulfill their roles as 'abd Allah (servants of God) and khalifah fi al-ardh (vicegerents on earth), and achieve a balanced integration of worldly responsibility and spiritual fulfillment. These findings demonstrate that the Qur'anic framework of Islamic education offers an integrative paradigm that harmonizes spiritual, intellectual, moral, and social dimensions, making it highly relevant for addressing contemporary educational challenges.